Social media in interventional radiology. Issue 2 (27th January 2021) - Wang, Michael T.; Foo, Michelle; Maingard, Julian; Kok, Hong Kuan; Lamanna, Anthony; Jhamb, Ashu; Brooks, Mark; Asadi, Hamed
Abstract: Introduction: Social media provides opportunities for Interventional Radiologists to share research, communicate with colleagues, provide health information and advertise their clinical practice. This study aims to examine the online and social media presence of currently practicing Australian Interventional Radiologists. Methods: Systematic Google searches were undertaken in May 2019 and updated in May 2020 to identify practicing Interventional Radiologists in Australia. Comprehensive searches of practice websites and social media platforms (Facebook, LinkedIn, Twitter, ResearchGate, YouTube) were undertaken for each Interventional Radiologist. Results: There were 265 Interventional Radiologists identified as currently practising in Australia, including 209 Interventional Radiologists (excluding Interventional Neuroradiologists), 49 Interventional Neuroradiologists and 7 that practise across both Interventional Radiology and Interventional Neuroradiology. 72% of Interventional Radiologists had at least one social media account, with LinkedIn the most widely used social media platform (60%). There was a significant negative correlation between the total number of social media accounts and years in practice ( P = 0.04). Across the states, a higher population per IR was positively correlated with a higher average number of social media accounts per IR ( P = 0.04). Interventional Neuroradiologists had a significantly higher average number of social media accounts compared to Interventional Radiologists (1.94 vs 1.29, P < 0.01). Conclusions: Most Australian Interventional Radiologists have a readily identifiable social media presence. There is potential for further utilisation of social media for academic, educational and business purposes.